Seleção de habitats por tatus no Parque Estadual Serra do Rola Moça, Minas Gerais - Cristina Apolônia Oliveira Santos (2011)
The majority of armadillo species have not been subjected to ecological and behavioral studies in their natural habitats. Armadillos are mostly nocturnal and are hard to observe and capture. A method that has proven useful in studying these animals is to examine the burrows they create, which may indicate which genera are present in a particular area and provide information regarding the selection and use of habitat. The current study was carried out in the Serra do Rola Moça State Park, which is located in an area of transition between the Cerrado and the Atlantic Forest biomes in Brazil. The research objectives were: a) To verify whether or not there are differences in habitat use among armadillo genera in different habitat types and; b) To determine the environmental variables that may influence habitat selection. Habitat selection was investigated in 18 areas within three distinct habitat types: grassland, cerrado and gallery forest. The locations of armadillo burrows were documented and subsequently described with respect to their substrate, physical appearence, and age. The genus of the armadillo species responsible for each burrow was identified whenever possible. To evaluate the factors that may influence the abundance of armadillo burrows in a given area, the characteristics of each locality were analyzed according to geographic, environmental and microhabitat descriptors. Soil samples were collected to measure the relative percentage of water and granulometric composition. 551 burrows were documented, of which, 380 were identified as having been created by species belonging to three different genera: Dasypus, Euphractus and Cabassous. Burrows were significantly more frequent in forested areas. Granulometric parameters did not allow a precise differentiation between the soil samples collected from the three habitat types when considered together. However, by considering the average diameter of soil granules and the graphic asymmetry, it was possible to differentiate between grassland and forest habitats, with forested areas showing higher proportions of fine particles in the soil. There was a significant association between the average soil granule diameter and the frequency of occurence and average depth of burrows. Habitat characteristics were not useful predictors of the frequency of burrows, with the exception of variable canopy cover.